Teosofi dalam Timbangan Ahlusunnah: Mengurai Kontroversi dan Menakar Batas Penyimpangan - Neyla Himmatul Ulya; Zahara Zahratul Jannah; Rizqiyatul Mardliyah; Shofil Fikri (Mazalat: Jurnal Pemikiran Islam, 2026)
Theosophy as a spiritual-esoteric approach has given rise to various controversies in the Ahlusunnah tradition, mainly because of accusations of deviations such as heresy, zindiq, and heresy. The main criticism focuses on theosophy's tendency to combine elements across traditions, the use of metaphysical speculation, as well as an overemphasis on inner experience that has the potential to displace the authority of revelation. From the point of view of fiqh, theosophy is considered to be at risk of ignoring the dimension of sharia, while from the perspective of kalam, it is considered to open up space for interpretations that are not in line with the principles of faith. In this context, this study aims to examine the roots of theosophy controversy in the perspective of Ahlusunnah, identify points of tension between esotericism and Islamic orthodoxy, and formulate proportional limits. This research uses a qualitative approach to library research with a normative-theological approach; descriptive-analytical analysis of primary (Qur'an, hadith, scholarly works) and secondary (academic literature) data. Thus, the inner dimension in Islam can still be developed without going out of the valid theological corridor and various accusations such as bid'ah, zindiq, and heresy are rooted in epistemological concerns; Theosophy can only be accepted on a limited basis on the condition that it does not contradict tauhid, sharia, and manhaj of scholars.